Disclosing Influencer Marketing on YouTube to Children: The Moderating Role of Para-Social Relationship - Boerman, Sophie C.; van Reijmersdal, Eva A. (Frontiers in Psychology, 2020)
Watching online videos is becoming an important part of children’s media diets. Children particularly like content that is specifically created for YouTube by YouTube personalities. Because these personalities have a large reach and are considered likeable and credible, they have become social media influencers. For advertisers, these influencers are an interesting channel to reach youth. Therefore, influencers often embed persuasive sponsored messages in their videos to earn money. However, there are concerns about this practice because it is not always clear when a video includes advertising. Therefore, in several countries, guidelines have been developed that state that sponsoring in influencer videos should be disclosed as such. Until now, little is known about the effects of disclosures for influencer videos on children and the boundary conditions for such effects. Therefore, we investigated the effects of a disclosure of sponsored influencer videos on children’s advertising literacy. Additionally, we examined the consequences of the disclosure for children’s responses to the brand, advertised product, and video. We also included the para-social relationship that children experience with an influencer as a possible boundary condition for disclosure effects on persuasion. Our experiment amongst children between 8 and 12 years old showed that, when children correctly recalled the disclosure, the disclosure activated their recognition of advertising, and understanding of selling and persuasive intent. Moreover, advertising literacy evoked by the disclosure affected persuasion: The disclosure enhanced brand memory through ad recognition, but also decreased advertised product desire through understanding the selling intent of the video. Furthermore, the para-social relationship of children with the influencer proved to be a boundary condition for disclosure effects on brand attitudes. Only for those children who experienced moderate to low para-social relationships with the influencer, the disclosure resulted in less positive brand attitudes through understanding selling intent. For children who experienced a strong para-social relationship with the influencer, the understanding that the content had a selling intent did not affect their brand attitudes. These findings show that a disclosure (if noticed and remembered) can be an effective tool to achieve transparency, but also influences the persuasive outcomes of influencer marketing in online videos.